2022
DOI: 10.1002/cjoc.202200486
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking G‐Quadruplexes as Targets and Tools against COVID‐19

Abstract: Comprehensive Summary The applicability of G‐quadruplexes (G4s) as antiviral targets, therapeutic agents and diagnostic tools for coronavirus disease 2019 (COVID‐19) is currently being evaluated, which has drawn the extensive attention of the scientific community. During the COVID‐19 pandemic, research in this field is rapidly accumulating. In this review, we summarize the latest achievements and breakthroughs in the use of G4s as antiviral targets, therapeutic agents and diagnostic tools for COVID‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…We found that the equal splitting (6–6 mode) yielded the maximum fluorescence, presumedly attributed to a more stable binding with the linker. Additionally, it is worth noting that the catalytic efficiency of split G4 for ThT is even much higher than that of intact G4, which might be due to the fact that compared with the antiparallel topological structure of intact G4, the hybrid conformation of split G4 is more stable in binding with ThT, and the folding process of intact G4 to form G4 structure is slower, indicating that split G4 is more suitable for constructing signal output mode. , Given that the steric hindrance effect between the two separated split G4 parts might influence the reassembly, we designed several kinds of linker strands with different spacer lengths (Figure C). We observed that the linker strand with a four-nucleotide spacer (L4) showed the best performance (Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the equal splitting (6–6 mode) yielded the maximum fluorescence, presumedly attributed to a more stable binding with the linker. Additionally, it is worth noting that the catalytic efficiency of split G4 for ThT is even much higher than that of intact G4, which might be due to the fact that compared with the antiparallel topological structure of intact G4, the hybrid conformation of split G4 is more stable in binding with ThT, and the folding process of intact G4 to form G4 structure is slower, indicating that split G4 is more suitable for constructing signal output mode. , Given that the steric hindrance effect between the two separated split G4 parts might influence the reassembly, we designed several kinds of linker strands with different spacer lengths (Figure C). We observed that the linker strand with a four-nucleotide spacer (L4) showed the best performance (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…34 For instance, G-quadruplex (G4) can serve as a label-free catalytic "light-up" reporter, through binding some effective small molecule substrates such as thioflavin T (ThT) and protoporphyrin IX (PPIX), to enhance the fluorescence output. 35,36 However, it takes a long time (up to several hours) for activated CRISPR/ Cas system to trans-cleave G4 structures due to steric hindrance and high topological stability. 33 As a transformational form, split G4 consisting of two or more nucleic acid segments of G4 could reassemble with the aid of the ssDNA linker, maintaining high catalytic efficiency and low background but allowing for more efficient cutting through CRISPR/Cas system and a more flexible modular design of signal reporters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plitidepsin, a cyclic peptide derived from marine sources, has demonstrated inhibition of SARS-CoV-2 by targeting eukaryotic translation elongation factor eEF1A ( White et al., 2021 ). We and others have demonstrated that RNA G-quadruplex (RG4), a non-canonical RNA secondary structure within guanine-rich sequences, is widely presented in both SARS-CoV-2 and host factors, including ACE2, AXL, furin, and TMPRSS2, and plays an important role in virus pathogenesis ( Liu et al., 2020 ; Qin et al., 2022 ; Liu et al., 2022a ; Tong et al., 2023 ). Intriguingly, Topotecan (TPT) and Berbamine (BBM) can function as RG4-stabilizing agents, thereby reducing the expression of RG4-containing host factors and SARS-CoV-2 infection ( Liu et al., 2022a ; Tong et al., 2023 ).…”
Section: Treatments Targeting Host Factorsmentioning
confidence: 99%
“…M-Blue has been shown to inhibit the entry of SARS-CoV-2 spike-bearing pseudovirus into ACE2-expressing cells [257]. Qin et al give an overview of the current advancements in stabilizing G4s in SARS-CoV-2 [258]. They emphasize the need for continual study to advance the progress in targeting G4s as a viable therapeutic avenue.…”
Section: Coronavirusesmentioning
confidence: 99%